Wage dispersion and technology: A firm-level analysis on European data - Valeria Cirillo; Matteo Sostero; Federico Tamagni (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2016)
Within-firm wage dispersion represents a relevant dimension of the overall wage inequality. A large stream of literature has analysed the wage-technology link without explicitly taking into account within-firm wage dispersion. In this work we aim to empirically investigate how technology affects within-firm wage dispersion and how it changes according to employer size. By exploiting employer-employee data from a survey of European firms (Eurostat's Structure of Earnings Survey - 2010) matched with information on sector innovation derived from the Community Innovation Survey, we look at the impact of innovation across small and medium-large firms, both on the average wages paid by firms and on the degree of within-firm wage inequality. Furthermore, we distinguish between high-paying and low-paying firms and more equal and unequal firms by means of a quantile regression approach.
Keywords: J31; O30; C21; 330; Wage inequalities; innovation; quantile regressions; employer-employees matched data